Estudo da eco-eficiência de argamassas e concretos reciclados com resíduos de estações de tratamento de água e de construções e demolições - Souza, Francis Rodrigues de (Universidade Federal de São Carlos, 2006)
Traditional and recycled mortar and concrete have been produced and the results from simple compression strength and water absorption tests have been compared. Recycled mortar and concrete have been produced out of sludge from water treatment plants and rubble from construction and demolition. The amount of aluminum present in the leached extract from the solubilization process of the concrete produced with the addition of both sludge from water treatment plants and rubble from construction and demolition has been determined. In terms of simple compression strength, the addition of up to 4 % of sludge in mass in place of natural sand has made it possible to obtain recycled concrete with similar characteristics to traditional concrete. Although water absorption of concrete and mortar produced from both sludge from water treatment plants and rubble from construction and demolition is much higher than water absorption of traditional mortar and concrete, the results have not made it impossible to use them; it has just restricted their application to places free from moist resulting from weather conditions or use characteristics. The leached extract resulting from the solubilization of the concrete produced out of both sludge from water treatment plants and rubble from construction and demolition has shown aluminum concentration higher than the drinkability standard defined by the Brazilian standards agency (ABNT), but not in such a level to turn the rubble from the recycled product dangerous to human health.
Study of eco-efficiency of mortar and concrete recycled from sludge from water treatment plants and rubble from construction and demolition
Keywords: Construção civil; Resíduos de construção e demolição; Lodo; Água - estações de tratamento; Sludge from water treatment plants; Rubble from construction and demolition; Concrete; Mortar; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL